Influence of volatiles-char interactions between coal and biomass on the volatiles released, resulting char structure and reactivity during co-pyrolysis. (15th November 2017) - Hu, Junhao; Si, Yaohui; Yang, Haiping; Shao, Jingai; Wang, Xianhua; Lei, Tingzhou; Agblevor, Foster A.; Chen, Hanping
Graphical abstract: Highlights: Coal/biomass char decreased the CH4, CO, and aromatics in biomass/coal volatiles. Biomass char was more effective than coal char to convert tars into gases. Volatiles interactions resulted in more ordered char structure. Volatiles interactions reduced the char reactivity of coal more easily than biomass. Abstract: The volatiles-char interactions are an important phenomenon in almost all existing pyrolysis/gasification processes. These interactions can affect almost all aspects of pyrolysis/gasification processes significantly. This study explores the influence of the volatiles-char interactions between the coal and biomass on the volatiles released, the resulting char structure, and the reactivity during co-pyrolysis. The interactions of biomass pyrolysis volatiles-nascent coal char and coal pyrolysis volatiles-nascent biomass char were studied at 800 °C in a two-stage fixed bed reactor. The product yields, gas composition, tar composition, Raman structure, and gasification reactivity of the resulting char were investigated. The results show that the presence of char promoted tar conversion into non-condensable gases during the volatiles-char interactions between the coal and biomass. For biomass volatiles with coal char interaction, the gas products were CO2, CH4, and CO whose concentrations decreased, and H2, whose concentration increased. Concerning the liquid products, the ketones, esters, phenols, and furans contents increased, whereas the aromatics content decreased. However, for coal volatiles with biomass char interaction, the concentrations of CO2 and H2 in the gas products and the content of furans in the liquid products showed the opposite trend. In addition, in the presence of biomass or coal volatiles, the larger aromatic ring systems in coal or biomass char grew, resulting in a decrease in the gasification reactivity. The volatiles-char interactions had a stronger influence on decreasing the reactivity of coal char than biomass char.